Spin-based ionic materials and devices for neuromorphic computing - Tan, Sze Han (Nanyang Technological University, 2020)
With the increasing demand for faster and cheaper chips, the conventional von Neumann architectures no longer able to fulfil these conditions. Neuromorphic computing inspired by neural systems could change the way things work now. Here, I emulate the synapse with a three-terminal cobalt transistor and ionic liquid gating. The usage of ionic liquid exploiting the high mobility of ions and the formation of electric double layers at interfaces produce high capacitance. The cobalt device exhibits non-volatile multilevel states, and by varying gate voltage, we can achieve resistance modulation. The pulsed voltage to represent the presynaptic spikes occurring in the neurons. The changing of the number of pulses, duration of pulses and the pulse width will realise the synaptic functions. The study of metal with ionic liquid gating will be interesting for future studies on ionic liquid and its implementation in neuromorphic circuits.